Non-infectious causes of pre-weaning mortality in piglets - Muns, R.; Nuntapaitoon, M.; Tummaruk, P. (Livestock science, 2016)
Piglet pre-weaning mortality (PWM) is one of the major reproductive components that affects herd productivity in the swine industry. Knowledge of factors that influence piglet PWM are important to improve animal welfare, to reduce production loss and to raise profits in commercial herds. The main objective of the present work was to review the most important non-infectious causes of piglet PWM and to present the main factors influencing them under commercial conditions. Piglet pre-weaning mortality is a multifactorial process, the small size of piglets at birth, together with their low body energy storage and their immature immune system, make them prone to chilling, starving, or being crushed by the sow. In general, factors causing piglet PWM are usually classified into three major groups: piglet (i.e., birth weight, vitality, and gender), sow (i.e., colostrum, parity, maternal stress, and sow nutrition), and environmental factors (i.e., season and temperature, housing, and management). Birth weight is the most determinant factor for piglet survival with direct impact on thermoregulatory capacity and growth; piglet vitality is also correlated with survival and growth and is strongly influenced by the degree of intra-partum hypoxia suffered by the piglet; additionally, piglet PWM appears to be sex-biased, with males showing greater susceptibility to causal mortality factors. Newborn piglets are highly dependent on colostrum to use it as energy substrate for thermoregulation and growth, and also to acquire passive immunity crucial for their future survival; however, sows' parity is a factor with contradictory effect on PWM which requires further research; a proper sows' comfort is also important for maternal stress around farrowing might have a negative impact on offsprings development and also increases the risk of crushing; sows' nutrition will influence foetal development and piglet birth weight, and is determinant to ensure a proper colostrum/milk production. Finally, ambient temperature has an important impact on piglet survival because piglets are very sensitive to cold stress. The housing system used in the farrowing room seems to influence the incidence of crushing. Promising results have been obtained using recent designs that combine initial confinement of the sow with the subsequent ability to move within the same pen. Different management strategies to deal with PWM are usually performed by producers around farrowing. However, there is a lack of scientific evidence on techniques, such as oral supplementation of piglets, cross-fostering, nurse sow systems, or artificial rearing of piglets, and further research should be of interest. •Piglet pre-weaning mortality is affecting herd productivity in swine industry.•Factors causing piglet pre-weaning mortality include piglet, sow, and environmental factors.•Birth body weight strongly influences piglet survival and thermoregulation ability.•Piglets' vitality determines piglets' capacity to suckle and compete for a teat.•Growth and survival rate of piglets is clearly associated with colostrum intake.